Merengkuh Kesemestaan - Albertus Bagus Laksana (Reformed Center for Religion and Society, 2023)
The book La grâce du végétal presents unique and fresh theological reasoning regarding the “divine economy”. The world of plants or vegetation is a blessing not only for themselves but also for other creatures, including humans, in relationships. In the ecological crisis, it is increasingly recognized that plants are